2020
DOI: 10.1186/s41065-020-00158-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mRNA expression level of RELN in peripheral blood of schizophrenia patients before and after antipsychotic treatment

Abstract: Background The Reelin (RELN) gene encodes the protein reelin, which is a large extracellular matrix glycoprotein that plays a key role in brain development. Additionally, this protein may be involved in memory formation, neurotransmission, and synaptic plasticity, which have been shown to be disrupted in schizophrenia (SCZ). A decreasing trend in the expression of RELN mRNA in the brain and peripheral blood of SCZ patients has been observed. There is a need to determine whether changes in RELN … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Beyond these genetic changes, there is a consistent and reproducible reduction in Reelin protein and RNA in postmortem SZ brains [166][167][168], with a reduction of up to 50% in some regions of the brain [169]. In addition, decreased levels of Reelin, of its mRNA, or of Reelin's regulatory transcription factor early growth response protein (ERG1) have been reported in the peripheral blood of schizophrenia patients when compared to healthy controls, and the levels were up-regulated following 12 weeks of treatment with antipsychotics [166,170,171]. Although peripheral blood levels of Reelin might not reflect the levels in the brain, these results are in favor of a dysregulation of the protein or its pathways in SCZ.…”
Section: Reelin In Schizophreniamentioning
confidence: 84%
“…Beyond these genetic changes, there is a consistent and reproducible reduction in Reelin protein and RNA in postmortem SZ brains [166][167][168], with a reduction of up to 50% in some regions of the brain [169]. In addition, decreased levels of Reelin, of its mRNA, or of Reelin's regulatory transcription factor early growth response protein (ERG1) have been reported in the peripheral blood of schizophrenia patients when compared to healthy controls, and the levels were up-regulated following 12 weeks of treatment with antipsychotics [166,170,171]. Although peripheral blood levels of Reelin might not reflect the levels in the brain, these results are in favor of a dysregulation of the protein or its pathways in SCZ.…”
Section: Reelin In Schizophreniamentioning
confidence: 84%
“…Moreover, reelin plasma levels did not correlate with biomarkers of liver status, which were within normal ranges in the AUD group. Alternatively, alterations in reelin could be reflecting medication effects, as some studies have reported altered reelin levels in patients treated with antipsychotic or antidepressant treatments ( Fatemi et al, 2009 ; Yin et al, 2020 ). In this study, disulfiram was the most frequently used medication (83.3%) in the AUD group, followed by antidepressants (45.8%), so we cannot rule out the potential effects of these medications; this limitation should therefore be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Reports indicate reelin's potential role in schizophrenia development, possibly due to its impact on the laminar structure of the cortex and synaptic signaling, which in turn would result in changes in the expression of reelin in the CNS and serum as well as changes in the expression of its receptors during treatment [26][27][28][29][30][31][32]45]. Currently, systematic research is needed to link the clinical effects of treatment with changes in the reelin signaling pathway as the primary target of antipsychotic therapy.…”
Section: Physiological Significance Of Reelin In Cnsmentioning
confidence: 99%
“…Intriguingly, schizophrenic patients exhibited significantly elevated serum levels of major reelin isoforms [29]. Furthermore, alterations in the activity of reelin-specific receptors, such as very low-density lipoprotein receptor (VLDLR) and apolipoprotein E receptor type 2 (Apo-ER2), were noted during antipsychotic treatment [30][31][32]. Drawing on available studies from PubMed and Scopus, our review delves into publications exploring the dysfunction of the reelin signaling pathway, Cajal-Retzius cells, and GABAergic interneurons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation